Restructuring of Political, Economic, Social and Technological Factors: Implication on Sustainable Funding of University Education in Nigeria - MUSA, Hazrat Maimuna; IBRAHIM, Yusuf (Ilorin Journal of Education, 2024)
University education in Nigeria is saddled with numerous surmountable problems which make the realization of the National objectives and those of the university difficult. Some of those problems range from inadequate infrastructural facilities, poor staff and students’ welfare service, issue of brain-drain among others have bearing on the lingering issues between the federal government and various unions in the universities resulting to incessant strike actions by the unions. Experiences in most Nigerian universities could be described by a critic as “teaching centers”, devoid of research and knowledge creation. The massive expansion and proliferation of the Nigerian university system without adequate policy on the revitalization for sustainable funding poses national challenges among which the production of high quality graduates who will compete favourably with their counterparts globally is unforeseeable in the nearest future. With all these expositions made, one is left without any doubt that the university education in Nigeria is in a serious crisis. Hence, the purpose of this study is to critically investigate the political, economic, social and technological (PEST) factors hindering achievements for sustainable funding of university education in Nigeria. The research method for the study is qualitative, using secondary sources of data. The study pointed out that low funding of education by the government was largely due to population explosion, socio-economic downtrodden, inefficient application of funds, policy inconsistency, endemic corruption and marked preference for other priorities among others negatively affects funding of university education. Therefore this paper concluded by making appropriate recommendations for sustainable funding of university education in Nigeria.